2003
DOI: 10.1038/nmat1012
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocarbon analogues of boron clusters — planarity, aromaticity and antiaromaticity

Abstract: An interesting feature of elemental boron and boron compounds is the occurrence of highly symmetric icosahedral clusters. The rich chemistry of boron is also dominated by three-dimensional cage structures. Despite its proximity to carbon in the periodic table, elemental boron clusters have been scarcely studied experimentally and their structures and chemical bonding have not been fully elucidated. Here we report experimental and theoretical evidence that small boron clusters prefer planar structures and exhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

47
675
4
8

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 686 publications
(734 citation statements)
references
References 43 publications
47
675
4
8
Order By: Relevance
“…After the prediction of stable, quasi-planar and tubular clusters of elemental boron, 1-4 which could later be confirmed experimentally, [5][6][7] materials scientist have started to search for boron nanostructures similar to graphene and carbon nanotubes. Several models for boron sheets and nanotubes (BNTs) with different underlying lattice structures have been proposed [8][9][10][11][12][13] and first successes in growing pure BNTs were reported.…”
Section: Introductionmentioning
confidence: 99%
“…After the prediction of stable, quasi-planar and tubular clusters of elemental boron, 1-4 which could later be confirmed experimentally, [5][6][7] materials scientist have started to search for boron nanostructures similar to graphene and carbon nanotubes. Several models for boron sheets and nanotubes (BNTs) with different underlying lattice structures have been proposed [8][9][10][11][12][13] and first successes in growing pure BNTs were reported.…”
Section: Introductionmentioning
confidence: 99%
“…the well-known α-B 12 and γ-B 28 crystals) although the B 12 icosahedron is not stable when it is treated as a single isolated cluster. [21][22][23][24] Recently, boron-rich ternary compounds containing B 12 icosahedra have attracted considerable attention since they exhibit important features on both fundamental and practical perspectives. [7,9,12,[25][26][27] For crystal boron, the central unit (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The α-boron crystal consists of eight B 12 icosahedra centered on the vertices of a rhombohedral unit cell, whereas the main structural motif in the B 105 unit cell of the β-boron is a B 84 polyhedron, where a central icosahedron is surrounded by twelve B 6 pentagonal pyramids, and these large B 84 soccer ball clusters are placed at the points of the rhombohedral lattice [7]. Although the natural phases of bulk boron do not possess laminar structures, recent experimental studies [8] confirmed the existence of quasiplanar clusters of 10-15 B atoms which have been previously predicted by first principle calculations [9]. Furthermore, single walled boron nanotubes (SWBNTs) have also been declared beforehand by Boustani and coworkers [10][11][12][13] which have also been synthesized experimentally [14,15] a few years ago with a radius of nearly 18Å, after the fabrication of crystalline [16] and amorphous [17] boron nanowires with diameters as small as 20 nm.…”
Section: Introductionmentioning
confidence: 99%